2015
DOI: 10.11648/j.ijefm.20150305.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information System on Upstream Supply Chain Management Among Supermarkets in Nakuru Town, Kenya

Abstract: Abstract:This study was conducted to find out the effect of Information Systems on Upstream Supply Chain Management. It determined the effect of ERO on Upstream Supply Chain Management and the effect of EDI on Upstream Supply Chain Management among supermarkets within Nakuru town. This study involved all the 9 supermarkets in Nakuru town. The primary data on information systems, enterprise resource planning and upstream supply chain management was collected using structured questionnaires with research items o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Each time these policy instruments change, banks operations and financial performance are affected (Al-Jarrah et al, 2010;Mulwa, 2015;Udeh, 2015). However, Kolapo, Ayeni, & Oke (2012), Kimani (2013), Kigandi (2014), Khan, & Sattar (2014), Agha (2014) and Muya & Gathogo (2016) are of the view that a commercial bank must be profitable for its long-term survival. A case in point is when the U.S commercial banks' net interest margin (NIM) declined significantly from 4.04 percent in 1999 to 3.03 percent in 2016 and rose again to 3.14 percent in 2017(World Bank, 2018.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Each time these policy instruments change, banks operations and financial performance are affected (Al-Jarrah et al, 2010;Mulwa, 2015;Udeh, 2015). However, Kolapo, Ayeni, & Oke (2012), Kimani (2013), Kigandi (2014), Khan, & Sattar (2014), Agha (2014) and Muya & Gathogo (2016) are of the view that a commercial bank must be profitable for its long-term survival. A case in point is when the U.S commercial banks' net interest margin (NIM) declined significantly from 4.04 percent in 1999 to 3.03 percent in 2016 and rose again to 3.14 percent in 2017(World Bank, 2018.…”
Section: Background Of the Studymentioning
confidence: 99%
“…This study involved all the 9 supermarkets in Nakuru town. The recommended that organizations, especially fast moving inventory should take a strategic approach to adoption of information systems concerned with supply chain management [6]. They also concluded that the implementation of Supply Chain Management Software involves expensive alterations and customizations in the organization and therefore organizations have to be strategic in adopting these systems.…”
Section: Related Workmentioning
confidence: 99%